Breast Ultrasound Image Improvement By Pixel Compounding of Compression Sequence - Yang, Zhi (2009)
Pixel compounding is a technique that synthesizes the information of an image sequence involving slow decorrelation of the speckle to form a detail-recovered and speckle reduced image. To avoid extra data acquisition time and patient exposure, reuse of the existing data is desirable. In the procedure of elasticity imaging, a set of B-mode images with slight changes due to deformation is produced, which provides an ideal input for the pixel compounding. The improvement in image quality is evaluated quantitatively using a figure-of-merit (FOM) that indicates the goodness of boundary information recovery and the contrast-to-noise ratio (CNR) over the phantom images. The increase in average CNR is from 0.4 in the original images to 0.8 in the pixel compounded images. The improvement in average FOM is from 0.15 to over 0.5 on a scale of 0 to 1. In vivo results with a breast cyst, a fibroadenoma, and a breast cancer are also presented and the image quality improvement is subjectively evaluated. The results suggest that B-mode breast images from compression procedures are suitable data for pixel compounding, and that a speckle reduced and detail-recovered or detail-maintained image can be produced. The improved imaging may provide alternative or better information for detection and diagnosis. A similar approach could be extended to elasticity imaging with other modalities.